Augmented Reality in Healthcare: A Review of Applications and Challenges - Zorzal, Ezequiel Roberto; Nunes, Fátima de Lourdes dos Santos (Proceedings of the Brazilian Symposium on Computing Applied to Health (SBCAS), 2014)
Augmented Reality can be applied in various areas of knowledge, and healthcare has been one of the most investigated fields. The objective of this paper is to present an analysis of Augmented Reality applications for health, considering the specialties that have been explored as well as the challenges of these specialties. 76 papers that presented research focused on the application of Augmented Reality in health were analyzed. These studies were classified according to the area of specialization, and the application goals. The results indicated that the most exploited specialties are Physiotherapy and rehabilitation, Radiology, Anatomy, Orthopedics and Cardiology that the main challenges are related to the problem the realism and registration of virtual objects into the real environment. It appears that there are still several challenges to be addressed, why Augmented Reality in Healthcare continues to offer many opportunities for research.